Teaching profession and praxis in Geography Teaching: reflections from supervised internship in a high school in Delmiro Gouveia/AL / A profissão docente e a práxis do Ensino de Geografia: reflexões a partir do estágio supervisionado em uma escola pública de Delmiro Gouveia/AL - Mayara Gomes de Oliveira; Leônidas de Santana Marques (Universidade Estadual de Alagoas, 2019)
In general, supervised internship is an important contact between the professional context and undergraduate students. In this article, an undergraduate student in Geography developed a workshop for students in a high school about Cartography. The experience obtained through this activity was organized in three parts: reflections about teaching profession; discussions in relation to the praxis of Geography teaching; and socialization of student reports that were produced during the workshop, resulting in significant learning. In this way, we understood that the content became more comprehensible than before, considering different methodological strategies that was adopted by the undergraduate student, resulting in a successful practice of Geography teaching.